2022
DOI: 10.1002/ejhf.2613
|View full text |Cite
|
Sign up to set email alerts
|

Guideline‐directed medical therapy in patients undergoing transcatheter edge‐to‐edge repair for secondary mitral regurgitation

Abstract: Aims Guideline‐directed medical therapy (GDMT), based on the combination of beta‐blockers (BB), renin–angiotensin system inhibitors (RASI), and mineralocorticoid receptor antagonists (MRA), is known to have a major impact on the outcome of patients with heart failure with reduced ejection fraction (HFrEF). Although GDMT is recommended prior to mitral valve transcatheter edge‐to‐edge repair (M‐TEER), not all patients tolerate it. We studied the association of GDMT prescription with survival in HFrEF patients un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Moreover, in EuroSMR, a European multicenter registry, including functional MR patients with left ventricular ejection fraction <50% indicated that triple-guideline-directed medical therapies, including MRAs, are associated with better survival after transcatheter edge-to-edge repair [ 21 ]. Therefore, the 2021 European Society of Cardiology as well as the 2022 American Heart Association/American College of Cardiology guidelines confirm the class I indication for mineralocorticoid receptor antagonist in patients with HF and a reduced left ventricular ejection fraction [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in EuroSMR, a European multicenter registry, including functional MR patients with left ventricular ejection fraction <50% indicated that triple-guideline-directed medical therapies, including MRAs, are associated with better survival after transcatheter edge-to-edge repair [ 21 ]. Therefore, the 2021 European Society of Cardiology as well as the 2022 American Heart Association/American College of Cardiology guidelines confirm the class I indication for mineralocorticoid receptor antagonist in patients with HF and a reduced left ventricular ejection fraction [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, given a correlative analysis, this study could not mechanistically provide the direct mechanism linking MRAs and myocardial dysfunction. In addition, the positive effect of Spiro and its high relevance for the treatment of heart failure over furosemide are well-known [ 21 , 22 , 26 ]. However, through this experimental model of MR we highlighted new insights of applications of heart failure drugs in mitigating the progression of MR and the possibilities of clinical interest for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the EuroSMR registry showed that among 1344 patients, beta‐blockers, renin–angiotensin system inhibitors, and mineralocorticoid receptor antagonists were prescribed in 1169 (87%), 1012 (75%), and 765 (57%) patients at the time of M‐TEER, respectively. Triple GDMT prescription was associated with a lower 2‐year all‐cause mortality compared to non‐triple GDMT (hazard ratio 0.74; 95% confidence interval 0.60–0.91) 31 …”
Section: Comorbiditiesmentioning
confidence: 96%
“…Triple GDMT prescription was associated with a lower 2-year all-cause mortality compared to non-triple GDMT (hazard ratio 0.74; 95% confidence interval 0.60-0.91). 31 An improvement in right ventricular (RV) function is associated with better outcome among patients with SMR undergoing M-TEER. 32 The short-term changes in tricuspid regurgitation (TR) .…”
Section: Valvular Heart Diseasementioning
confidence: 99%
“…Among 1344 patients with LVEF <50% and SMR undergoing M-TEER from a large European registry, the rates of baseline beta blockers, ACEi/ARB/ARNI and MRA prescription were 87%, 75% and 57%, respectively. Triple GDMT prescription was associated with better prognosis after M-TEER 107 . HF phenotypes of advanced disease [i.e.…”
Section: Comorbidities and Special Conditionsmentioning
confidence: 99%